Setting standards for improved syndromic surveillance. - Forslund, D.W.
Clearly, there is a need for data at multiple levels and many locations. Investigations of possible cases and outbreaks must occur locally, and local data must be available as generated to healthcare providers and emergency responders. At the same time, regional, national and international authorities need aggregated data to understand the scope of an outbreak and to assist in the response. Thus, in comparison to a system in which data is sent to a central facility for aggregation and redistributed to local areas, we argue that a distributed system is much more appropriate and resilient to a bioterrorism event. The distributed data system can provide information to local responders for their immediate action and reduce demand on a central system and data unavailability over wide area networks while providing raw data immediately to centralized reviewers.
Keywords: Aggregated data; Data unavailability; Distributed system; Federated approach; Improved syndromic surveillance; Interoperable standards; Medical surveillance; Open source; Public health threat; Standardized components; Surveillance software